PENGARUH UNDERWRITER, UMUR PERUSAHAAN, UKURAN PERUSAHAAN, PROFITABILITAS, FINANCIAL LEVERAGE, JENIS INDUSTRI TERHADAP UNDERPRICING (Studi pada Perusahaan yang Melakukan IPO yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2015) - Lisiantara, G. Anggana; Hanif Rifa’i, 13.05.52.0152 (Students' Journal of Accounting and Banking, 2017)
Underpricing is a phenomenon where stock prices at initial offerings are lower than those of stocks traded on the secondary market. Companies that do initial offer avoids the occurrence of underpricing, because the company does not get the maximum funds from the sale of its first stock. So this study aims to examine the factors - factors that affect the level of Underpricing period 2011 - 2015. The population used in this study are all companies that conduct Initial Public Offering in Indonesia Stock Exchange (BEI) in 2011 - 2015. The sample research is determined by purposive sampling method. The sample used is 90 companies. Hypothesis testing using multiple regression analysis. The result of this research model shows that (1) Underwriter has significant negative effect on underpricing; (2) The age of the Company has no effect on underpricing; (3) Company size does not affect underpricing; (4) Return On Assets (ROA) has no effect on underpricing; (5) Financial Leverage (FL) has no effect on underpricing (6) Industry type has no effect on underpricing. This means that the high underwriter variable can affect the underpricing level.Keywords: Underpricing, Underwiter, Age of Company, Company Size, Return On Assets (ROA), Financial leverage (FL), Industry Type